Serious Complications of Intraosseous Access during Infant Resuscitation - Molacek, Jiri; Houdek, Karel; Opatrný, Václav; Fremuth, Jiri; Sasek, Lumir; Treskova, Inka; Treska, Vladislav (European Journal of Pediatric Surgery Reports, 2018)
We report on a 2.5-month-old infant with ischemia of the left leg and compartment following intraosseous needle application during resuscitation. Unfortunately, this event led to major limb amputation. The cause, mechanism, and prevention of this severe complication are discussed in this article.
Keywords: intraosseous access; limb amputation; compartment syndrome